Idealism in Educational Philosophy: Reclaiming Values in an Age of Scientific Pragmatism - Mubin, Hakun; Nasrowi, Bagas Mukti; Hufron, M (Tadibia Islamika: Journal of Holistic Islamic Education, 2025)
Education, as a means of shaping humanity through human resource development, demands a comprehensive outlook that encompasses the full spectrum of human existence and potential. Addressing contemporary educational challenges requires more than practical experience; it necessitates critical thinking, rigorous scientific analysis, and sustained scholarly research. Additionally, education must be firmly grounded in philosophical discourse and reflective inquiry. As the foundational discipline underlying all sciences, philosophy seeks to resolve both existing and emerging human challenges, particularly those concerning the metaphysical triad of God, humanity, and nature. However, with the ongoing evolution of society and the acceleration of technological change, many contemporary issues have surpassed the explanatory capacity of traditional philosophy alone, leading to the emergence of empirical science as a complementary approach to understanding reality. The term "philosophy" originates from the ancient Greek philosophia, signifying "love of wisdom"—a synthesis of philos (to love) and sophia (wisdom). In its essence, philosophy embodies humanity's enduring quest for truth, meaning, and ethical understanding. The systematic study of philosophy enables individuals to confront life's multifaceted challenges with deeper insight and analytical sophistication, particularly within the complex domain of education. In this context, philosophy provides a foundational framework for educational thought and practice, serving to align pedagogical approaches with the broader aspirations and values of society. This paper explores the significance and application of idealism within the philosophy of education, examining how idealist principles—alongside other philosophical schools such as essentialism and radicalism—inform educational concepts, objectives, curriculum design, and instructional methodologies. Through qualitative descriptive analysis grounded in library research and philosophical inquiry, this study demonstrates that idealism continues to play a pivotal role in shaping educational values, moral development, and the intellectual orientation of contemporary educational systems.